DEVELOPMENT OF ELEMENTS OF FOOD MARKETS - Bahodirjon Nosirov, Akbarali Abdurashidov (Zeta Repository, 2023)
The development of wholesale markets in Uzbekistan is in the directions of their enlargement, deeper specialization, formation of market infrastructure, and their transformation into wholesale and distribution centers of food, which provide for the implementation of transactions only with standardized products. The main functions of all types of wholesale markets are organization and formation of conditions for independent small wholesale trade, organization of large wholesale transactions. The wholesale market is a component of the wholesale trade system and has an independent economic structure. Its task is to organize trade of agricultural raw materials and food products between independent sellers and buyers in certain places and on the basis of established rules. The activities of wholesale distribution centers include several functions: provision of sales areas, cooling chambers, warehouse facilities, and provision of transportation, advertising, informational, and other services. The wholesale market addresses these critical issues.